MAKNA FASIK DALAM QS. AL-BAQARAH AYAT 26-27: STUDI KOMPARATIF TAFSIR AL-MARĀGĪ DAN TAFSIR AL-MISBAH - Putri Azizah Rustan; Syarifah Awaliah Jazilah; Rahmi Damis (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2026)
This study examines the meaning of “fasik” in Surah Al-Baqarah/2:26–27 through a comparative analysis of the interpretations offered by Ahmad Mustafa al-Marāgī in Tafsir al-Marāgī and M. Quraish Shihab’s Tafsir al-Misbah. This study is motivated by the importance of the concept of fasik in the Qur’an as well as the limited number of studies that specifically compare the interpretations of these two exegetes regarding this verse. This study is a literature review(library research) employing a qualitative approach and utilizing the muqāran exegesis method. The results of the study show that both exegetes agree that fasik refers to the act of turning away from obedience to Allah after the arrival of guidance and truth. Both also identify three main characteristics of the fasik: violating Allah’s covenant, severing relationships that are commanded to be maintained, and causing corruption on earth. The difference lies in the emphasis of their interpretations. Al-Marāgī places greater emphasis on linguistic, rational, and historical approaches, whereas Quraish Shihab emphasizes moral, spiritual, and socio-contextual relevance. This study concludes that the concept of fasik in QS. Al-Baqarah/2:26–27 refers not only to sinners but also to individuals who consciously turn away from Allah’s guidance, thereby damaging their relationship with Allah, fellow human beings, and the environment.